Technology Enabled Stress Management Strategies for Athletes: A Psychological Analysis - Mark Smales, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
The basic purpose of research is to determine the technology-enabled stress management strategies for athletes. This research study based on psychological analysis also depends upon secondary research data based on data collected from different websites related to the athletes. Technology considers independent, and stress management strategies are the dependent variables. The psychological analysis considers as a mediator variable related to them. To determine the research, use E-views software and generate informative results related to the indicators. The descriptive statistical analysis, the unit root test analysis, the Dickey fuller test analysis, the histogram, and state analysis, also the graphical analysis between them. The overall result found that the technology shows a significant link in the stress management strategies for athletes. Technology plays a vital role in stress management strategies related to psychological analysis for athletes.